2018
DOI: 10.1002/jia2.25123
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing history and access to treatment among migrants living with HIV in Europe

Abstract: IntroductionMigrants are overrepresented in the European HIV epidemic. We aimed to understand the barriers and facilitators to HIV testing and current treatment and healthcare needs of migrants living with HIV in Europe.MethodsA cross‐sectional study was conducted in 57 HIV clinics in nine countries (Belgium, Germany, Greece, Italy, The Netherlands, Portugal, Spain, Switzerland and United Kingdom), July 2013 to July 2015. HIV‐positive patients were eligible for inclusion if they were as follows: 18 years or ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…However, migrant and non-migrant heterosexual participants were less likely to have had an HIV test before their HIV diagnosis and were more often diagnosed with a late-stage HIV infection than non-migrant MSM, indicating they are facing barriers in accessing HIV testing services. The finding that almost all participants visited a healthcare facility in the 2 years before HIV diagnosis but only in 40% an HIV test was discussed suggests that testing opportunities are being missed, as has been demonstrated at the European level [9]. In line with our findings, another study in the Netherlands found that HIV testing was often not discussed during GP consultations prior to HIV diagnosis [12].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, migrant and non-migrant heterosexual participants were less likely to have had an HIV test before their HIV diagnosis and were more often diagnosed with a late-stage HIV infection than non-migrant MSM, indicating they are facing barriers in accessing HIV testing services. The finding that almost all participants visited a healthcare facility in the 2 years before HIV diagnosis but only in 40% an HIV test was discussed suggests that testing opportunities are being missed, as has been demonstrated at the European level [9]. In line with our findings, another study in the Netherlands found that HIV testing was often not discussed during GP consultations prior to HIV diagnosis [12].…”
Section: Discussionsupporting
confidence: 85%
“…As previous studies have shown outcomes are influenced by sexual orientation [8, 9], participants were grouped into: migrant MSM, non-migrant MSM, migrant heterosexual men, non-migrant heterosexual men, migrant women and non-migrant women. Socio-demographic characteristics and non-dichotomous outcomes were compared between groups using chi-square tests and Fisher’s exact tests for categorical variables and one-way ANOVA (normally distributed) and Kruskal Wallis tests (not normally distributed) for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…PrEP uptake among heterosexual migrants in Europe so far has been extremely low [34,35]. Against this background, condomless sex in small sexual networks with high proportions of late diagnoses [36] may indeed serve as a relevant outcome. The odds of not using a condom in the host country was five times higher when the last sexual intercourse abroad was also condomless.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the major reasons for discontinuing ART were depression, wanting a break, and side effects [10]. In Ibidun paper, the experienced difficulties with health services in migrants living with HIV in Europe were no GP/health card/ insurance, long waiting time for an appointment/in the clinic, and lack of trust in GP confidentiality [11]. According to Laisaar et al's study, the main issues in HIV/AIDS patients engagement in HIV care in Estonia in 2013 were, as about one quarter of persons estimated to live with HIV had not been diagnosed, another quarter although aware of their HIV-positive status had not accessed HIV medical services, and more than half of HIV/AIDS patients having accessed HIV medical cares did not maintain in care.…”
Section: Discussionmentioning
confidence: 99%